Prevalence Of Hypertension and It's Correlates in Elderly Population of Coastal Karnataka - Shahul Hameed; Chethana K; Krutarth R Brahmbhatt; Dipak C Patil; Prasanna KS; Jayaram S (Medsci Publications, 2014)
Background: Hypertension is becoming an important public health problem worldwide. It exhibits iceberg phenomena were unknown morbidity exceeds the known morbidity. The prevalence of hypertension is rapidly increasing in developing countries and is said to be one of the leading causes of death and disability among the elderly. Objective: To determine the prevalence and factors influencing hypertension among geriatric population living in the rural community of coastal Karnataka. Methodology: A cross-sectional community-based study was conducted among elderly population aged 60 years and above residing in the rural community in the field practice area of A.J. Institute of Medical Sciences & Research Centre. A total of 330 subjects aged 60 years and above were randomly included by simple random sampling technique from a list of elderly subjects being maintained at the rural health training center. Using a structured questionnaire, the basic information and history regarding diagnosis and treatment of hypertension was collected. Blood pressure, height and weight were recorded. Result: Among the study population, the prevalence of hypertension was detected to be 58.5%. Among the 184 non-hypertensive subjects, 47 (25.5%) subjects were newly diagnosed as hypertensive. With logistic regression, hypertension cases were associated with age more than 70 [OR 1.754 95% CI 1.056-2.913] and occurrence of diabetes [OR 2.40 95% CI 1.286-4.510). Conclusions: Findings of this study emphasize the public health importance of hypertension in the elderly. There is a definite need for screening the elderly, especially diabetics for early diagnosis followed by regular treatment of hypertension to reduce the associated complications.